PENGARUH MODEL MULTILITERACY INTEGRATIVE LEARNING BERMUATAN ISU SOSIAL TERHADAP KETERAMPILAN MENULIS TEKS ANEKDOT SISWA KELAS X SMAN 3 PADANG - Puja Junifia; Vivi Indriyani; Nursaid; Emidar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low anecdotal text writing skills of grade X students of SMAN 3 Padang, which is reflected in students' difficulties in constructing systematic text structures and integrating elements of social criticism into intelligent humor. Most students are still fixated on writing ordinary humorous stories without sharp satire, and are hampered by the use of conventional learning models that do not stimulate multimodal creativity. To overcome these problems, this study applies the Multiliteracy Integrative Learning (MULGRANING) model with social issues. This model was chosen because of its ability to integrate various literacy modes, both visual, digital, and textual, with the context of social reality close to students' lives. This type of research is quantitative with a quasi-experimental method using a Control-Only Group Posttest Design. The study population includes all grade X students of SMAN 3 Padang in the 2024/2025 academic year. The sampling technique used purposive sampling, thus designating Phase E 9 as the experimental class, receiving the MULGRANING model, and Phase E 7 as the control class, using the conventional model. Research data were collected through an anecdotal text writing performance test, which was then assessed using an assessment rubric covering aspects of content, structure (abstract, orientation, crisis, reaction, coda), linguistic aspects, and humor/criticism. In conclusion, the Multiliteracy Integrative Learning model, which addresses social issues, is effective in improving students' creative writing competencies. This research has implications for the importance of pedagogical innovation that connects teaching materials with social phenomena in the digital era to create meaningful and contextual language learning.